Giant peritoneal loose body - case report - Rykovský, M; Michal, M (Rozhledy v chirurgii, 2023)
The article presents the case of a rare, free moving, completely benign intra-abdominal formation called "giant peritoneal loose body". In our case, an expansion of the left hypogastrium with central calcification, in intimate contact with intestinal loops, of rather benign etiology, reminiscent of a mesenteric calcifying fibrous tumor, was accidentally detected on CT angiography. A possible neoplastic process was suspected, and therefore PET/CT was completed, showing that the expansion had moved to the right hypogastrium, and the radiologist evaluated the finding as a possible teratoma not originating from an intestinal loop. Due to the still indeterminate nature of the expansion, an exploratory laparotomy was performed with the discovery of a loose ovoid mass without any vascular supply and unrelated to other structures, which was extracted and sent for histological examination. The result was surprising. According to the pathologist, it was a rare, completely benign intra-abdominal lesion called the "giant peritoneal loose body". This pseudotumor should be considered as a differential diagnosis whenever we accidentally detect an asymptomatic, freely moving intra-abdominal lesion with central necrosis or calcification, in order to avoid unnecessary surgery, because according to available information, only symptomatic ones should be surgically removed.
Keywords: Peritoneal Diseases; kalcinóza; Humans; Laparotomy; lidé; Calcinosis; giant peritoneal loose body; boiled egg; PET/CT; Tomography, X-Ray Computed; abdominal stalactite; Positron Emission Tomography Computed Tomography; nemoci peritonea; epiploic appendices; laparotomie; počítačová rentgenová tomografie